Progressive right ventricular dysfunction and exercise impairment in patients with heart failure and diabetes mellitus: insights from the T.O.S.CA. registry - Salzano, Andrea; D’Assante, Roberta; Iacoviello, Massimo; Triggiani, Vincenzo; Rengo, Giuseppe; Cacciatore, Francesco; Maiello, Ciro; Limongelli, Giuseppe; Masarone, Daniele; Sciacqua, Angela; Filardi, Pasquale Perrone; Mancini, Antonio; et al. (Cardiovascular diabetology, 2022)
Findings from the T.O.S.CA. Registry recently reported that patients with concomitant chronic heart failure (CHF) and impairment of insulin axis (either insulin resistance—IR or diabetes mellitus—T2D) display increased morbidity and mortality. However, little information is available on the relative impact of IR and T2D on cardiac structure and function, cardiopulmonary performance, and their longitudinal changes in CHF.
Gesehen am 29.08.2022